PENDIDIKAN KELUARGA DALAM PERSPEKTIF AL-QUR’AN (SURAT LUQMAN AYAT 12-19) - Karnila Karnila; Ivana Tazkia Jen (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
This study aims to explain about Family Education in the Perspective of the Qur'an (Sura Luqman Verses 12-19). The background of this study is the existence of a letter in the Qur'an which contains various ways of educating children to become human beings with noble character. The method used in this research is library research. The approach used is a descriptive analysis approach, which is an approach used to collect data and information with various materials found in the library, such as books and articles. The results of this study are that in Luqman's letter there are educational materials that can be applied by parents in the family, teachers in schools, and individuals in the community. The conclusion from family education in the perspective of the Qur'an consists of aqidah, shari'ah and morals education. The aspect of aqidah (faith) is the teaching of monotheism. The aspect of shari'ah is the teaching of worship. Akhlaq aspect is a teaching about behavior. This research is expected to be material for parents in family education issues